SOCIO-PHILOSOPHICAL ANALYSIS OF NATIONAL LIFESTYLE OPTIMIZATION - Boymurodov Zohid Shokirovich (Western European Studies, 2025)
The article is devoted to the transformation of the national lifestyle throughout the socio-historical development, its legalities and the analysis of modern tndences. The existence of different lifestyles during one period of socio-historical development, its causes and consequences have been analyzed. The role and importance of entrepreneurial activity in optimizing the national lifestyle has been studied.
Keywords: socio-historical development; environmental situation; economic factor